Jinmaitong, a Traditional Chinese Compound Prescription, Ameliorates the Streptozocin-Induced Diabetic Peripheral Neuropathy Rats by Increasing Sciatic Nerve IGF-1 and IGF-1R Expression - Song, Wei; Jiang, Wen; Wang, Chao; Xie, Jun; Liang, Xiaochun; Sun, Ying; Gong, Liyun; Liu, Wei; Qu, Ling (Frontiers in Pharmacology, 2019)
Jinmaitong (JMT) is a Traditional Chinese Compound Prescription for the treatment of diabetic peripheral neuropathy (DPN). This study aims to investigate the effect of JMT on insulin-like growth factor 1 (IGF-1) and insulin like growth factor 1 receptor (IGF-1R) expression in sciatic nerves of diabetic rats. Firstly, the chemical profile of JMT was characterized by UPLC/Q-TOF-MS analysis. A total of 72 compounds were putatively identified. Secondly, streptozotocin (STZ)-induced diabetic rats were treated with neurotropin (NTP, 2.67 NU/kg/day) or JMT at low-dosage (0.4375 g/kg/day), medium-dosage (0.875 g/kg/day) and high-dosage (1.75 g/kg/day) for continuous 16 weeks. Blood glucose and body weight were detected every four weeks during the experiment. The mechanical pain and morphological change on sciatic nerves were detected by pain measurement instrument and microscopy. The IGF-1 level in serum and tissues were measured though ELISA and immunohistochemistry. The mRNA and protein expressions of IGF-1, IGF-1R, peripheral myelin protein zero (P0) and peripheral myelin protein 22 (PMP22) in the tissues were measured by qRT-PCR and western blot. As a result, JMT had no significant effect on body weight, but reduced the fasting blood glucose levels of diabetic rats. Besides, the pathological morphology, mechanical pain thresholds, serum level and tissue expression of IGF-1, mRNA and protein levels of IGF-1R, P0 and PMP22 were significantly improved in JMT group at middle dosage. In conclusion, JMT could ameliorate the behavioristics and morphology changes in DPN rats by promoting IGF-1 and IGF-1R gene and protein expressions in sciatic nerves, as well as regulating the peripheral nerve remyelination genes P0 and PMP22 expressions, which provides scientific evidence for the clinical application of JMT in DPN patients.